Ge(Sn) growth on Si(001) by magnetron sputtering. (March 2021) - Khelidj, H.; Portavoce, A.; Bertoglio, M.; Descoins, M.; Patout, L.; Hoummada, K.; Hallén, A.; Charaï, A.; Benoudia, M.C.; Mangelinck, D.
Graphical abstract: Highlights: Sn-rich GeSn films were grown on Si(001) at high temperature by magnetron sputtering. Ge(Sn) crystallization temperature prevents to grow Sn-rich films without Sn islands. Relaxed pseudo-coherent Ge0.9 Sn0.1 films were in-situ grown on Si(001) at 633 K. Ge0.9 Sn0.1 monocrystalline films contain impurity concentrations below 2 × 10 19  cm −3 . Ge0.9 Sn0.1 monocrystalline films show a resistivity 10 4 times lower than that of Ge. Abstract: The semi-conductor Ge1― x Sn x exhibits interesting properties for optoelectronic applications. In particular, Ge1― x Sn x alloys with x ≥ 0.1 exhibit a direct band-gap, and integrated in complementary-metal-oxide-semiconductor (CMOS) technology, should allow the development of Si photonics. CMOS-compatible magnetron sputtering deposition was shown to produce monocrystalline Ge1― x Sn x films with good electrical properties at low cost. However, these layers were grown at low temperature (< 430 K) and contained less than 6 % of Sn. In this work, Ge1― x Sn x thin films were elaborated at higher temperature (> 600 K) on Si(001) by magnetron sputtering in order to produce low-cost and CMOS-compatible relaxed pseudo-coherent layers with x ≥ 0.1 exhibiting a better crystallinity. Ge1― x Sn x crystallization and Ge1― x Sn x crystal growth were investigated. Crystallization of an amorphous Ge1― x Sn x layer deposited on Si(001) or Ge(001) grown on Si(001) leads to the growth of polycrystalline films. Furthermore, the competition between Ge/Sn phase separation and Ge1― x Sn x growth prevents the formation of large-grain Sn-rich Ge1― x Sn x layers without the formation of β -Sn islands on the layer surface, due to significant atomic redistribution kinetics at the crystallization temperature ( T = 733 K for x  = 0.17). However, the growth at T = 633 K of a highly-relaxed pseudo-coherent Ge0.9 Sn0.1 film with low impurity concentrations (< 2 × 10 19 at cm ―3 ) and an electrical resistivity four orders of magnitude smaller than undoped Ge is demonstrated. Consequently, magnetron sputtering appears as an interesting technique for the integration of optoelectronic and photonic devices based on Ge1― x Sn x layers in the CMOS technology.